The relationship of testosterone levels with sprint performance in young professional track and field athletes - Bezuglov, E.; Ahmetov, I. I.; Lazarev, A.; Mskhalaya, G.; Talibov, O.; Ustinov, V.; Shoshorina, M.; Bogachko, E.; Azimi, V.; Morgans, R.; Hackney, A. C. (Physiology & Behavior, 2023)
Evidence suggests that higher testosterone levels may provide an athletic advantage. Therefore, it is of practical interest to examine the association between testosterone levels and power- and strength-related traits in young professional track and field athletes, and to consider the factors that determine testosterone levels. The study involved 68 young professional athletes (45 females, 17.3 ± 2.6 years; 23 males, 18.2 ± 1.9 years). Testosterone levels were assessed via liquid chromatography-mass spectrometry. All subjects performed two 20 m and two 30 m sprint trials, and countermovement jump without arm-swing. A bioimpedance analysis of body composition was carried out and biological maturity was examined using the Khamis-Roche method. The average testosterone levels were 26.4 ± 9.6 nmol/l and 1.5 ± 0.7 nmol/l in males and females, respectively. In female athletes, testosterone levels did not correlate with any of traits. Males with the highest testosterone levels were significantly faster in the 20 m (p = 0.033) and 30 m (p = 0.014) sprint trials compared to males with lower testosterone levels. Testosterone levels in males were positively associated with fat mass (p = 0.027), and degree of biological maturation (p = 0.003). In conclusion, we found a positive relationship between testosterone levels and sprint performance in young male athletes.